Municipal Solid Waste Management in Iceland: Case study of Plastic - Ahmed Ehab Mohamed Hamdy Ahmed 1991- (2024)
This study focuses on delineating the legal frameworks and methodologies for waste collection and management in Iceland. It seeks to highlight the predominant practices of waste collection and disposal within the country, with a special emphasis on the strategies employed for plastic waste management. Furthermore, the study explores how Iceland could leverage the advanced waste management experiences of other nations to enhance its own practices. Employing a quantitative approach and case study analysis, the research draws insights from municipal and national government records, alongside a review of numerous waste management sites across Iceland. Additionally, it incorporates findings from scientific articles addressing related research variables within the Icelandic context. Practical insights were garnered through interviews with ten municipal officials, each specializing in different facets of waste management. Analytical Hierarchy Process (AHP) analysis was utilized to ascertain the most effective method of managing plastic waste. Key findings indicate Iceland's predominant use of landfilling for waste disposal. The results also show that recycling with energy recovery is the method that can best improve plastic waste management in Iceland.